2021
DOI: 10.35774/econa2021.03.105
|View full text |Cite
|
Sign up to set email alerts
|

Investment in Innovative Development of Competitiveness of Resource and Production Potential of Mining Enterprises

Abstract: The subject of the research is the processes of ensuring the competitiveness of the potential of mining enterprises based on certain key aspects of methodology and practice of rational management of investment distribution, which are inherent in the investment and innovation activities of subsidiaries within the parent company. The purpose and objectives of the study is to improve theoretical and methodological approaches to increase the competitiveness of the potential of mining enterprises on the basis of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Для поглибленого оцінювання впливу ризику на загальну інтегровану оцінку можна рекомендувати використання показника "Евклідова відстань" -відхилення (міра відстані) інтегрованої оцінки ОТР від встановленого (визначеного) "еталонного" значення: гірничо-збагачувальне підприємство має достатньо високий техніко-технологічний рівень організації виробничо-економічних процесів. В інших випадках слід зосередити увагу на більш грунтовному аналізі щодо необхідності залучення інвестицій у розвиток техніко-технологічної бази підприємства та ефективності організації її використання [14].…”
Section: економічна наукаunclassified
“…Для поглибленого оцінювання впливу ризику на загальну інтегровану оцінку можна рекомендувати використання показника "Евклідова відстань" -відхилення (міра відстані) інтегрованої оцінки ОТР від встановленого (визначеного) "еталонного" значення: гірничо-збагачувальне підприємство має достатньо високий техніко-технологічний рівень організації виробничо-економічних процесів. В інших випадках слід зосередити увагу на більш грунтовному аналізі щодо необхідності залучення інвестицій у розвиток техніко-технологічної бази підприємства та ефективності організації її використання [14].…”
Section: економічна наукаunclassified
“…The analysis of literature sources showed that today the theoretical principles of forming the competitiveness of the resource potential of the enterprise are still insufficiently studied and the relevant conceptual features are not taken into account. Although there are some scientific developments on this issue, namely the works of such Ukrainian and foreign scientists as V. Gorbokon [3], O. Dobykina [10], S. Kapitula [1,2,4, 5], O. Korenkov [7], N. Mitsenko [8], A. Predein [11], O. Sushchenko [13] and others. However, despite such a wide range of scientists who have studied this issue, most aspects of the competitiveness of the resource potential of the enterprise still remain undiscovered, and therefore need further development.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…According to research by M. Adamenko et al (2021), which focuses on developing integrated digital models as a strategic tool for enhancing mining enterprises' competitiveness, it's important to consider adaptation strategies and potential difficulties in implementing integrated digital models in various mining enterprise contexts. Researchers A. Burkovskaya & Yu.…”
mentioning
confidence: 99%